2013
DOI: 10.1007/s12307-013-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Marker Expression of Carcinoma-Associated Fibroblasts (CAFs) in Patients with Epithelial Ovarian Carcinoma After Treatment with Neoadjuvant Chemotherapy

Abstract: Cancer-associated fibroblasts (CAFs) play an important role in tumor initiation and progression. The aim of this study is to explore the role of 2 CAF markers, fibroblast activated protein (FAP) and α-smooth muscle actin (αSMA), in patients with epithelial ovarian cancer (EOC) post-neoadjuvant chemotherapy. Sixty-six patients with the diagnosis of EOC treated with debulking surgery after neoadjuvant therapy were retrieved from the archives. Immunohistochemistry for FAP and αSMA antibodies were performed on par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
4
29
0
6
Order By: Relevance
“…Nevertheless, none of these genes showed signi cant association with HSOC survival. This result may be partly due to negative expression of αSMA (30).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, none of these genes showed signi cant association with HSOC survival. This result may be partly due to negative expression of αSMA (30).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast cells acquire phenotypes that are perpetually activated, and their identification is made by the expression of smooth muscle alpha-actin and alpha-activating protein of fibroblasts, which are called CAFs [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The fibroblasts associated with cancer manifest significance in tumor progression, structural and functional support in the tumor microenvironment. The population of CAFs is vast and is composed of several markers including the alpha-actin and smooth muscle alpha-actin activation protein [6, 18]. CAFs are responsible for the activation of fibroblasts that have biological significance in lymphangiogenesis, angiogenesis, tumorigenesis, cell degradation, extracellular matrix production and tumor invasion, and metastatic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between claudins (CLDN6 and CLDN10) expression and various immune cells in ltration of ovarian cancer were shown in Table 2. As shown in Relevant evidences reported that cancer associated broblast (CAF) plays an important role in the progression of ovarian cancer [24,25] . Interestingly, we also found that CAF has a positive correlation with CLDN6 expression, but a negative correlation with CLDN10 expression.…”
Section: Correlation Analysis Between Claudins and The Tumor Microenvmentioning
confidence: 94%